Redistributing deaths by ill-defined and unspecified causes on cancer mortality in Brazil - Bigoni,Alessandro (2021)
ABSTRACT OBJECTIVE to discuss the impact four different redistribution strategies have on the quantitative and temporal trends of cancer mortality assessment in Brazil. METHODOLOGY This study used anonymized and georeferenced data provided by the Brazilian Ministry of Health (BMoH). Four different approaches were used to conduct the redistribution of ill-defined deaths and garbage codes. Age-standardized mortality rates used the world population as reference. Prais-Winsten autoregression allowed the calculation of region, sex, and cancer type trends. RESULTS Death rates increased considerably in all regions after redistribution. Overall, Elisabeth B. França’s and the World Health Organization methods had a milder impact on trends and rate magnitudes when compared to the Global Burden of Disease (GBD) 2010 method. This study also observed that, when the BMoH dealt with the problem of redistributing ill-defined deaths, results were similar to those obtained by the GBD method. The redistribution methods also influenced the assessment of trends; however, differences were less pronounced. CONCLUSIONS Since developing a comparative gold standard is impossible, matching global techniques to local realities may be an alternative for methodological selection. In our study, the compatibility of the findings suggests how valid the GBD method is to the Brazilian context. However, caution is needed. Future studies should assess the impact of these methods as applied to the redistribution of deaths to type-specific neoplasms.